2020
DOI: 10.1021/acssuschemeng.0c01497
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Coprecipitation Directed Porous Core–Shell Mn–Co–O Catalyst for Efficient Low Temperature Propane Oxidation

Abstract: Mn–Co–O catalysts with different Mn/Co molar ratios were synthesized by means of a facile inverse coprecipitation strategy and applied for the oxidation of propane (C3H8). The XRD pattern of Co2Mn1Oδ (molar ratio of Mn:Co = 1:2) indicates a Co3O4 phase, and most Mn incorporates into Co3O4 lattice to form a solid solution. Minor distributed Mn species occur structure reforming, totally converting to a stable Co–Mn solid solution during oxidation process. Meanwhile, Co2Mn1Oδ features a porous core–shell morpholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…A similar mixture of MnO x and CoO x phases was also described for Mn-Co-O catalysts with different Mn/Co molar ratios. 17,29 A thorough analysis of the samples containing Co 3 O 4 revealed that there was a shi to lower values of 2q with the increase of Mn : Co molar ratio, indicating an increase of the lattice cell parameters (Table S1 †), similar effect has been described in previous works. 30,31 For instance, the lattice parameter a is 8.09 nm in the sample Co 3 O 4 and increased accordingly to 8.11, 8.12, and 8.13 nm in Mn@Co 3 O 4 -1, Mn@Co 3 O 4 -2, and Mn@Co 3 O 4 -3, respectively.…”
Section: Oer Electrocatalytic Performance Of the Lmssupporting
confidence: 80%
See 2 more Smart Citations
“…A similar mixture of MnO x and CoO x phases was also described for Mn-Co-O catalysts with different Mn/Co molar ratios. 17,29 A thorough analysis of the samples containing Co 3 O 4 revealed that there was a shi to lower values of 2q with the increase of Mn : Co molar ratio, indicating an increase of the lattice cell parameters (Table S1 †), similar effect has been described in previous works. 30,31 For instance, the lattice parameter a is 8.09 nm in the sample Co 3 O 4 and increased accordingly to 8.11, 8.12, and 8.13 nm in Mn@Co 3 O 4 -1, Mn@Co 3 O 4 -2, and Mn@Co 3 O 4 -3, respectively.…”
Section: Oer Electrocatalytic Performance Of the Lmssupporting
confidence: 80%
“…A similar mixture of MnO x and CoO x phases was also described for Mn–Co–O catalysts with different Mn/Co molar ratios. 17,29…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Doping other transition metals into Co 3 O 4 has been extensively studied to improve catalytic activity. The metal dopant can affect the surface oxygen property by changing the geometric and electronic properties of the host metal oxide. For example, In doping changed the chemical states of chemisorbed oxygen on Co 3 O 4 surfaces, improving the surface oxygen mobility, resulting in promoted activity for CO oxidation. , Also, Ni doping into Co 3 O 4 could enhance the catalytic activity for propane oxidation. , In particular, Mn has been considered to significantly improve the activity of Co 3 O 4 for various catalytic oxidations. The Mn doping could generate more active oxygen species on the Co 3 O 4 surface, resulting in improved activity. The strong interaction between Mn and Co also improved the structural stability of the catalyst surface. , However, depending on the surface structures of Co 3 O 4 , the specific coordinations between Co and O were different, affecting the surface oxygen properties. The effect of metal doping depending on the surface structure has not been clearly revealed. We hypothesized that the doping feature would vary for different surface structures of Co 3 O 4 .…”
Section: Introductionmentioning
confidence: 99%
“…According to the elemental components (Table ) and diffraction peaks (Figure ) of the derived catalysts, reduction peaks of ZnCr-2 and ZnCr-3 were shifted to lower temperatures with the increase in Cu and Zn contents. Reduction peaks derived from Mn and Ni were distributed at 300–500 °C. , If the peak belonged to Ni, it was a large-particle bulk NiO, which was weakly linked to the carrier (such as ZnCr-1). Otherwise, the peak was the reduction of Mn 3+ to Mn 2+ (such as ZnCr-2 and ZnCr-3).…”
Section: Resultsmentioning
confidence: 99%